A methodology for Local Economy-Wide Impact Evaluation (LEWIE) of cash transfers - J. Edward Taylor (International Policy Centre for Inclusive Growth (IPC-IG), 2012)
(...) This paper presents a methodology to understand the full impact of cash transfers on local economies, including on the production activities of both beneficiary and non-beneficiary groups; how these effects change when programmes are scaled up to larger regions; and why these effects happen. All of these are important for designing projects and explaining their likely impacts to governments and other sponsoring agencies. The simulation methods presented here are not a substitute for good impact evaluations. Experimental findings are important to test and quantify the likely impacts of interventions on beneficiary households and, under some conditions, on ineligible households. They can also help validate some of the predictions of simulation models and, in some cases, improve the accuracy of model parameters. Validation is a strength of conventional experimental methods but a major concern in GE modelling. We econometrically estimate the LEWIE model parameters and use Monte Carlo methods to perform significance tests and construct confidence intervals around project impact simulation results. We believe that this is an important step towards providing simulation impact evaluation with validation tools that are largely absent in the GE literature.
Keywords: 330